2013
DOI: 10.1186/1752-153x-7-82
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysis in heterocyclic synthesis: DABCO as a mild and efficient catalytic system for the synthesis of a novel class of quinazoline, thiazolo [3,2-a]quinazoline and thiazolo[2,3-b] quinazoline derivatives

Abstract: BackgroundThere are only limited publications devoted to the synthesis of especially thiazolo[3,2-a]quinazoline which involved reaction of 2-mercaptopropargyl quinazolin-4-one with various aryl iodides catalyzed by Pd-Cu or by condensation of 2-mercapto-4-oxoquinazoline with chloroacetic acid, inspite of this procedure was also reported in the literature to afford the thiazolo [2,3-b] quinazoline. So the multistep synthesis of the thiazolo[3,2-a]- quinazoline suffered from some flaws and in this study we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In earlier investigations we developed methods for the efficient synthesis of a variety of polyfunctional azoles, azines and their fused derivatives [32,33,34,35,36]. Recent efforts in our laboratories have led to the design of new and general strategies for the preparation of 2-amino-5-arylazo-nicotinates and pyridazinones [37] that involve reactions of 3-oxo-2-arylhydrazonopropanals 1 with active methylene compounds, including ethyl cyanoacetate, and malononitrile, depending on the effect of the substituent present in the arylazo moiety.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier investigations we developed methods for the efficient synthesis of a variety of polyfunctional azoles, azines and their fused derivatives [32,33,34,35,36]. Recent efforts in our laboratories have led to the design of new and general strategies for the preparation of 2-amino-5-arylazo-nicotinates and pyridazinones [37] that involve reactions of 3-oxo-2-arylhydrazonopropanals 1 with active methylene compounds, including ethyl cyanoacetate, and malononitrile, depending on the effect of the substituent present in the arylazo moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, thiazole and quinolone are privileged structures in the designing of a fused thiazoloquinazoline system, which is predictable to biodynamic properties with characteristic features. However, literature revealed a growing demand for the development of new syntheticprocesses includingpotential synthesisofactive substituted thiazole quinazoline systems like thiazolo[3,2-a]quinazoline, thiazolo[2,3-b]quinazoline, thiazolo[4,3-b]quinazoline, thiazolo[5,4-c]quinoline thiazolo[5,4-f]quinazoline, and thiazolo[4,5-h]quinazolin [ 31 ]. Moreover, after the extensive literature survey of the aforesaid, it was observed that there has been an increasing focus in the chemistry ofthiazolo[2,3-b]quinazoline because of the capability to exhibit an enormous variety of biological and pharmacological activities [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among known catalytic [7][8][9][10] and noncatalytic [11][12][13] synthetic approaches to the targeted heterocyclic system, the most interesting was that based on the condensation of substituted 2-halobenzoyl chlorides with 2-aminothiazole [14] (Scheme 1). This approach implies the use of a substrate containing an activated halogen substituent in the 2-position.…”
mentioning
confidence: 99%